Phenomenological Initiative in the Design Program of a Modern Architect. On the example of the Park of Future Generations in Yakutsk - Dobritsyna, Irina A. (Actual Problems of Theory and History of Art, 2020)
The article deals with the actual problems of architectural phenomenology, which asserts the superiority of cultural and aesthetic criteria in architecture over technocratic ones in the post-industrial era.The phenomenological paradigm defines the turn to a new strategy for designing the urban environment in the 21st century and renews interest in the theory of ‘place’ in architecture. The article reveals the meaning of the modern stage of development of the theory of ‘place’, shows the possibility of compromise-in preserving the spiritual meaning of a person’s place of residence against the background of technological improvementof design and construction.The subject of the research is the modern theory of ‘place’ within the system of phenomenological studies of architecture. The research aims to show the significance of the theory of ‘place’ for the architectural theory and practice of the 21st century. Objectives are to reveal the meaning of the current stage of the development of the theory of ‘place’; to show the possibilities of the compromise in preserving the spiritual sense of the place of human residence, against the background of the technological improvement of design and construction spheres.To compare the current condition of the environment with the prototypes of the long history of the man’s dwelling places; to find out the possibilities of activating the ‘sense of ‘place’’ in the modern architectural design.Methods of analysis — following the Norwegian theorist C. Norberg-Schulz, who poetically developed the modern understanding of the ‘place’, the philosophical and theoretical ascent of the problem is considered.The multi-dimensional concept of Stimmung by the Canadian theorist A. Perez-Gomez, which reveals a modern step in the theoretical substantiation of the significance of phenomenological problems for the sphere of project ideas, is clarified.For the sake of understanding of the idea of ‘place’ in modern conditions as well as clarification of the nature of the architect’s work in creating not just a template, but a sensually unique phenomenon of the environment,an example from the design practice of one of the Russian architectural workshops — the Moscow‘ATRIUM’ bureau is analyzed.The final idea: 1) modern architecture is able to articulate the unique existential space; 2) the symbolization of the unique position of a person in the natural and social world while paying attention to traditions becomes one of the most important tasks for architecture in Russia and abroad against the background of the increasing technological complexity of the environment.
Keywords: mood; environment; place; atmosphere; the “sense of the place” theory; Christian Norberg-Schulz; Alberto Perez-Gomez; ATRIUM; Yakutia